Investigation of Surface Hardness and Microstructural Changes in S45C Carbon Steel Cylinders Through Arc Quenching - Pham Son Minh; Van-Thuc Nguyen; Thanh Tan Nguyen; Nguyen Ho (Metals)
Arc quenching has many advantages, including generating large amounts of heat in a short time, a self-quenching ability, and simple equipment. The electric arc energy from a TIG welding machine was used to modify the surface properties of S45C Carbon Steel Cylinders. The study focuses on the impact of arc length, current intensity, travel speed, gas flow rate, heating angle, and pulse on surface hardness after arc quenching an S45C steel tube with a cylinder surface. The study found that the hardness reduces from 45.1 HRC to 41.2 HRC as the current intensity increases from 125 A to 140 A. According to Taguchi’s results, the ranking of factors which have the greatest impact on surface hardness are pulse time, travel speed, intensity, gas flow rate, arc length, and heating angle. The pulse time has the highest impact because it directly influences the heating input, followed by the travel speed. Arc length and heating angle, on the other hand, have the least effect. The base metal, heat-affected area, and hardened area are the three distinct areas that make up the microstructure structure. After the arc quenching process, the case hardening depth is represented by the heat-affected zone at 1536 μm. A highly colored residual austenite and a needle-shaped martensite phase make up the hardened region. The hardened region is 1200 μm thick and has a hardness of more than 300 HV0.3. The study’s findings may improve the application and understanding of the arc quenching treatment procedure in the industrial sector.